Anterior tibial compartment syndrome following prolonged tetany - Lees, A. J. (1976)
A patient developed a persistent, disabling, bilateral anterior tibial compartment syndrome after salicylate self-poisoning. Prolonged tetany is postulated as the probable mechanism.